AP Ir. Dr. Mohd Hafizi research receives MTE 2021 Special Award - Nor Salwana, Mohammad Idris (2021)
PEKAN, 1 April 2021 – The research by Associate Professor Ir. Dr. Mohd Hafizi Zohari titled Fiber Bragg Grating System for Engineering Structures Health Monitoring received the MTE 2021 Chinese Innovation & Invention Society Taiwan Special Award and a gold medal in the Malaysia Technology Expo 2021 (MTE) held online recently.